2017
DOI: 10.5964/ijpr.v11i1.254
|View full text |Cite
|
Sign up to set email alerts
|

Your responses guide me: Decreased attachment anxiety through an online relationship-building paradigm

Abstract: This study aims to improve self-reported attachment anxiety and avoidance through an online relationship-building paradigm. Seventyseven undergraduate participants completed an online attachment-focused paradigm in which they developed a relationship with a virtual partner, and fifty participants successfully completed a second laboratory-based phase of the study. During the online phase, all participants completed the Experiences in Close Relationships-Revised questionnaire (ECR-R), the experimental group eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Showing that anxiety may bring about a predisposition to perceive the social environment of same-sex others competitively, is in line with the notion that experiencing childhood instability leads to the development of a fast life history strategy and attachment anxiety (Dunkel et al, 2016). On the same line, a recent study of virtual relationship building (Johnson & Bliwise, 2017), found that the effects of building a virtual relationship decreased attachment anxiety but had not effect in attachment security or avoidance, which is consistent with the notion that attachment anxiety is correlated with poor relational skills such as a competitive approach to same sex others.…”
Section: Discussionsupporting
confidence: 65%
“…Showing that anxiety may bring about a predisposition to perceive the social environment of same-sex others competitively, is in line with the notion that experiencing childhood instability leads to the development of a fast life history strategy and attachment anxiety (Dunkel et al, 2016). On the same line, a recent study of virtual relationship building (Johnson & Bliwise, 2017), found that the effects of building a virtual relationship decreased attachment anxiety but had not effect in attachment security or avoidance, which is consistent with the notion that attachment anxiety is correlated with poor relational skills such as a competitive approach to same sex others.…”
Section: Discussionsupporting
confidence: 65%
“…To test Hypothesis 3, multiple linear regression (with contrast coded [for categorical variables] and mean centered [for continuous variables] predictors) was utilized to evaluate interaction effects between attachment dimensions and sex in predicting TBQ scale scores. As attachment anxiety and avoidance were moderately correlated (Undergraduate: r = .31, , .001; MTurk: r = .67, p , .001), we controlled for the other dimension in these analyses, consistent with prior research (Johnson & Bliwise, 2017). We did not make alpha adjustments to the primary models, but used a Bonferroni alpha correction for the posthoc pairwise comparisons of stress response analyzed in the repeated measures ANOVA for interpretation of mean differences.…”
Section: Data Analysis Planmentioning
confidence: 99%